Upaya Edukasi Pengetahuan Remaja Dalam Peningkatan Budaya Hidup Sehat di Sekolah Menengah Atas Swasta Amanah Tahfidz Deliserdang - Sri Lasmawanti; Maya Ardila Siregar; Maria Haryanti Butar butar (CV. ULIL ALBAB CORP, 2024)
A healthy life is a life that can be said to be a carefree life or living in a prosperous state, namely physical, psychological, social and spiritual health according to Law No. 23 of 1993 concerning Health, which states that health is a state of physical, mental and social well-being that makes life possible. socially and economically productive. Health must be seen as a unified whole consisting of physical, mental and social elements in which mental health is an integral part of health. Healthy living is also very influential, especially in teenagers. Routine activities for teenagers that support health and are carried out regularly by teenagers so that they are always in a healthy condition include thinking, emotions, movement and exercise, nutrition and social and spiritual aspects. Cultivating a healthy lifestyle will have an impact on reducing all causes of death and increasing lifespan and well-being. A healthy lifestyle culture will also provide the opportunity to be independent for longer in old age. Through good understanding, it is hoped that it can give birth to thoughts that motivate oneself to carry out activities that are good for health so that a culture of healthy living will support every daily activity among teenagers and support them in achieving achievements. It is important to monitor and evaluate the impact of these efforts periodically to ensure continued behavior change and improvements in the culture of healthy living in the school environment. Apart from that, collaboration between schools, parents and communities is key in creating an environment that supports the implementation of a healthy living culture among teenagers.